Insights into the species diversity of the genus Sargassum (Phaeophyceae) in the Mediterranean Sea, with a focus on a pre-viously unnoticed taxon from Algeria - AOUISSI, MOUNIA; SELLAM, LOUIZA NESRINE; BOUDOURESQUE, CHARLES F.; BLANFUNÉ, AURELIE; DERBAL, FARID; FRIHI, HOCINE; PERRET-BOUDOURESQUE, MICHELE; REBZANI-ZAHAF, CHAFIKA; VERLAQUE, MARC; THIBAUT, THIERRY (Mediterranean Marine Science, 2018)
Nine currently accepted species of the genus Sargassum (Phaeophyceae) have been recorded from the Mediterranean Sea: S. acinarium, S. desfontainesii, S. flavifolium, S. furcatum, S. hornschuchii, S. muticum, S. ramentaceum, S. trichocarpum and S. vulgare. Two of them, S. desfontainesii and S. furcatum, are Atlantic species, the Mediterranean range of which is restricted to the Alboran Sea, close to the Strait of Gibraltar. Three species, S. hornschuchii, S. ramentaceum and S. trichocarpum are endemic to the Mediterranean. The presence of S. flavifolium in the Mediterranean, a north-eastern Atlantic species, is at least in part based upon a misidentification and therefore requires confirmation. A taxon collected near Algiers and Annaba (Algeria), here referred to as ‘Sargassum sp. from Algeria’, although sharing most characters with S. flavifolium, also presents some distinctive characters. In the absence of genetic data, confirming or not its taxonomic value, and in the lack of studies on the herbaria containing the types of many species currently considered as synonyms of S. flavifolium, but which are possible candidates for accommodating the Algerian specimens, the authors prefer a conservative approach. They do not describe a new species, which would be premature, but draw attention to a taxon which may be more widely distributed in the Mediterranean rather than solely along the Algerian coasts.